Asylum law in the European Union - Cherubini, Francesco, 1975- (London : Routledge, 2015)
This work examines the rules governing the right to asylum in the European Union. The book analyses a number of sources of law including international law, EU law and the case law of the European Court of Human Rights. The book considers the 1951 United Nations Convention relating to the Status of Refugees and the 1967 Protocol in order to understand the degree to which asylum obligations under international refugee law have been incorporated into the European Union. The book has a particular focus on the prohibition of refoulement the main obligation the EU law must confront. The dual nature of this principle is explored looking at both the obligation imposed upon a state to provide a fair procedure to determine the conditions of risk in the country of origin or destination, and also the obligation to refrain from or to respond to a possible expulsion. Through this investigation the book sheds light on the EU competence on asylum in relation to the different position of Members States
The Geneva Convention of 1951 and Its Protocol of 1967 -- The 1950 Rome Convention and Its Protocols -- Evolution of EC and EU Competences for Asylum -- International Protection in EU Legislation -- Conclusions.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Evropská unie; právo azylu; right of asylum; země Evropské unie; European Union countries; e-knihy online; e-books online